Hubungan Dukungan Sosial Dengan Kualitas Hidup Orang Dengan HIV/AIDS (ODHA) Di RSUD Sekarwangi - Srivani Nur Ismillah; Hendri Hadiyanto; Arfatul Makiyah (Jurnal Ventilator, 2024)
Human Immunodeficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) are chronic infectious diseases. HIV/AIDS not only causes physical problems, but can also affect an individual's social and psychological problems. Stigma and discrimination are social problems that exist in the environment around people living with HIV/AIDS (PLWHA), so they cause a decrease in the quality of life for HIV/AIDS sufferers. The existence of social support from the surrounding environment in the form of emotional support allows PLWHA to improve their health status so as to achieve a better quality of life. This research aims to determine the relationship between social support and the quality of life of people living with HIV/AIDS (PLWHA) at Sekarwangi Regional Hospital. This research uses a correlational descriptive quantitative method with a cross-sectional approach. Using a questionnaire with accidental sampling data collection techniques with a total of 72 respondents. Results: Based on the results of the analysis using the Chi square statistical test, it was found that p=0.000 < ?=0.05, Ha was accepted, which means there is a relationship between social support and the quality of life of people with HIV/AIDS (PLWHA) at the Sekarwangi Regional General Hospital. The research conclusion is that there is a significant relationship between social support and the quality of life of people living with HIV/AIDS (PLWHA) at Sekarwangi Regional Hospital.